2003
DOI: 10.1002/pros.10279
|View full text |Cite
|
Sign up to set email alerts
|

Increased growth factor production in a human prostatic stromal cell culture model caused by hypoxia

Abstract: Prostatic stromal cells respond to hypoxia by upregulation of secretion of several growth factors suggesting that hypoxia can trigger prostatic growth. Therefore, hypoxia might be a key factor contributing to the pathogenesis of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 41 publications
6
64
0
4
Order By: Relevance
“…In addition, increased expression of bFGF has been recently described in stromal cells cultured under hypoxic conditions. 39 Finally, HIF-1␣-dependent alterations of heparan sulfate proteoglycan (HS) composition on the EC surface, which enhance the cell responsiveness to bFGF, has also been demonstrated, 40 further emphasizing the connection between hypoxia, HIF-1␣, and bFGF. 41,42 It remains to be established whether HIF-1-dependent induction of bFGF observed under our experimental conditions is …”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased expression of bFGF has been recently described in stromal cells cultured under hypoxic conditions. 39 Finally, HIF-1␣-dependent alterations of heparan sulfate proteoglycan (HS) composition on the EC surface, which enhance the cell responsiveness to bFGF, has also been demonstrated, 40 further emphasizing the connection between hypoxia, HIF-1␣, and bFGF. 41,42 It remains to be established whether HIF-1-dependent induction of bFGF observed under our experimental conditions is …”
Section: Discussionmentioning
confidence: 99%
“…FGFs are also found in this gradient pattern and ectopic FGF expression caused abnormal coronary patterning within the ventricular wall (Pennisi and Mikawa, 2005). FGF family members are increased in their expression and secreted under hypoxic conditions in other systems (Berger et al, 2003;Moeller et al, 2004). Many factors important in coronary vessel formation are known to be hypoxia inducible and/or controlled directly or indirectly by HIF-1 in other systems.…”
Section: Regulation Of Cardiac Blood Vessel Developmentmentioning
confidence: 99%
“…17,18 Berger et al showed that the production of several growth factors to increase in human prostatic stromal cells by hypoxia, thus playing an important role in the development of prostate hypertrophy. 19 In the present study, we developed a unique culture system to evaluate tumor-stromal cell interaction under hypoxia. Using this system, we analyzed whether hypoxia enhances the invasive activity of pancreatic cancer cells, while also increasing some secretions from fibroblasts, thus leading to the activation of cancer invasion.…”
mentioning
confidence: 99%